Volumetric measurements are preferred in the evaluation of mutant IDH inhibition in non-enhancing diffuse gliomas: Evidence from a phase I trial of ivosidenib. Issue 5 (9th November 2021) - Ellingson, Benjamin M; Kim, Grace Hyun J; Brown, Matt; Lee, Jihey; Salamon, Noriko; Steelman, Lori; Hassan, Islam; Pandya, Shuchi S; Chun, Saewon; Linetsky, Michael; Yoo, Bryan; Wen, Patrick Y; et al.
Abstract: Background: Since IDH-mutant (mIDH) low-grade gliomas (LGGs) progress slowly and have a relatively long survival, there is a significant need for earlier measurements of clinical benefit. Guidance using the LGG RANO criteria recommends serial bidirectional (2D) measurements on a single slice; however, questions remain as to whether volumetric (3D) measurements are better, since they would allow for more accurate measurements in irregular shaped lesions and allow readers to better assess areas of subtle change. Methods: Twenty-one (out of 24) non-enhancing, recurrent mIDH1 LGGs were enrolled in a phase I, multicenter, open-label study of oral ivosidenib (NCT02073994), and with imaging pre- and post-treatment as part of this exploratory ad hoc analysis. 2D and 3D measurements on T2-weighted FLAIR images were centrally evaluated at an imaging contract research organization using a paired read and forced adjudication paradigm. The effects of 2D vs 3D measurements on progression-free survival (PFS), growth rate measurement variability, and reader concordance and adjudication rates were quantified. Results: 3D volumetric measurements showed significantly longer estimated PFS ( P = .0181), more stable ( P = .0063) and considerably slower measures of tumor growth rate ( P = .0037), the highest inter-reader agreement (weighted kappa = 0.7057), and significantly lower reader discordance rates ( P = .0002) with 2D LGG RANO. Conclusion: 3D volumetric measurements are better for determining response assessment in LGGs due to more stable measures of tumor growth rates (ie, less "yo-yo-ing" of measurements over time), highest inter-reader agreement, and lowest reader discordance rates. Continued evaluation in future studies is warranted to determine whether these measurements reflect clinical benefit.